Freeze-thaw resistant fiber recycled aggregate roller compacted concrete as well as preparation method and application thereof
By adding silica fume, fly ash, water-absorbent seafoam fibers and composite antifreeze to the regenerated aggregate rolling concrete, combined with vibration rolling construction, the problems of low strength and poor anti-freeze and thawing performance of regenerated aggregate are solved, and the problem of low strength and poor anti-freeze and thawing performance of regenerated aggregate is achieved. It efficiently improves the mechanical properties and durability of concrete and is suitable for large-scale construction applications.
Patent Information
- Application Number
- CN202411459182.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing recycled aggregate concrete has low strength due to the presence of old mortar on the surface and microcracks on the inside, making it difficult to effectively improve its mechanical properties and freeze-thaw resistance in large-scale applications.
The recycled aggregate rolling concrete technology of anti-freeze-thaw fiber recycled aggregate is used to remove defects on the surface of the recycled aggregate through reasonable proportions of silica fume and fly ash, and add water-absorbing seafoam fibers and composite antifreeze to improve crack resistance and durability. And improve the compactness and freeze-thaw resistance of concrete through vibration rolling construction.
It significantly improves the compressive strength, crack resistance and durability of fiber recycled aggregate rolled concrete, enhances its mechanical properties and water retention under freeze-thaw cycle conditions, realizes efficient resource utilization of building waste, and reduces Construction costs and energy consumption.
Smart Images

Figure CN119219386A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycled aggregate concrete, and specifically relates to a freeze-thaw resistant fiber recycled aggregate roller compacted concrete and a preparation method thereof, and also relates to the application of the freeze-thaw resistant fiber recycled aggregate roller compacted concrete. Background Art
[0002] With the continuous increase in urbanization rate, the speed of construction industry renewal is gradually accelerating, and the resulting construction waste emissions are also rising year by year. Such a huge amount of construction waste has become a major problem facing economic and social development. Recycled concrete technology is the most common and efficient way to utilize construction waste resources. However, due to the bonding of old mortar on the surface of recycled aggregates and a large number of microcracks inside, recycled concrete has defects such as low strength. Current methods to improve its defects include aggregate strengthening, fiber addition, and external constraints. However, these technologies have high preparation costs, great construction difficulties, and low performance stability, which limits large-scale applications.
[0003] Roller-compacted concrete is a type of ultra-dry hard concrete with less water consumption per unit and a slump close to zero. It is constructed by pouring thin layers through the warehouse and vibrating and rolling. The use of recycled aggregate to prepare roller-compacted concrete can reduce the amount of mixing water and improve the strength of roller-compacted concrete. Combining fiber with recycled aggregate roller-compacted concrete, a new fiber-recycled aggregate roller-compacted concrete technology is proposed, which significantly improves the flexural strength, impact resistance and wear resistance of the new material, and can be widely used in new road construction, industrial floors, ports and docks, etc. At the same time, considering that it is used in most areas of these scenarios, it will be affected by periodic changes in temperature. The basic mechanical properties of the concrete matrix will be greatly reduced due to the cyclical damage of freezing and thawing, and the durability of the concrete material will also be seriously affected.
[0004] Based on this, a freeze-thaw resistant fiber recycled aggregate roller compacted concrete and a preparation method thereof are provided, and vibration rolling method is used to replace the traditional pouring method to prepare fiber recycled aggregate roller compacted concrete with excellent mechanical properties and freeze-thaw resistance. It can not only provide a new solution for the disposal of construction waste and the utilization of recycled aggregates, but also comply with the national development strategy of "carbon peak and carbon neutrality". It can be foreseen that this technology has broad application prospects. Summary of the invention
[0005] One of the purposes of the present invention is to provide a freeze-thaw resistant fiber recycled aggregate roller compacted concrete.
[0006] The second object of the present invention is to provide a method for preparing freeze-thaw resistant fiber recycled aggregate roller compacted concrete.
[0007] The third object of the present invention is to provide an application of freeze-thaw resistant fiber recycled aggregate roller compacted concrete.
[0008] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a freeze-thaw resistant fiber recycled aggregate rolled concrete, which is composed of the following raw materials by weight: 400-455 parts of rolled recycled coarse aggregate; 140-160 parts of cement; 14-18 parts of silica fume; 30-38 parts of fly ash; 195-225 parts of natural aggregate; 50-65 parts of water-absorbing sepiolite fiber; 50-70 parts of water; 2-4 parts of composite fiber aggregate; 1.25-3.6 parts of composite antifreeze agent; 1-1.5 parts of polycarboxylic acid high-performance water reducer; The composite antifreeze agent is composed of the following raw materials by weight: 0.05-0.15 parts of ethylene glycol; 0.05-0.15 parts of sodium thiocyanate; 0.04-0.08 parts of sodium oxalate; 0.1-0.2 parts of polyglycerol fatty acid ester; 0.01-0.05 parts of sodium gluconate; and 1-3 parts of water.
[0009] The general idea of the present invention is as follows: In the raw materials of the freeze-thaw resistant fiber recycled aggregate RCC provided by the present invention, adding a reasonable proportion of silica fume and fly ash can effectively remove the original defects such as loose and fragile old mortar and a large number of cracks on the surface of the recycled coarse aggregate, thereby improving its material strength and the performance of the obtained concrete; a reasonable proportion of composite fiber aggregate can significantly improve the early crack resistance, splitting strength, flexural strength and durability of the recycled concrete. In addition, in order to improve the freeze-thaw resistance of the fiber recycled aggregate RCC, the present invention also provides a composite antifreeze agent, with ethylene glycol, sodium thiocyanate and sodium oxalate as the main antifreeze components, ethylene glycol is combined with polyglycerol fatty acid ester, polycarboxylic acid high-performance water reducer and sodium gluconate, which can improve the bubbles introduced into the concrete during the mixing process and make them evenly arranged, thereby enhancing the water retention and fluidity of the concrete.
[0010] Furthermore, the water-absorbent sepiolite fiber added to the raw materials of the present invention has certain adsorption, fluidity and good durability. It can play the following roles when added to the fiber-recycled aggregate concrete: first, due to the high adsorption of the water-absorbent sepiolite fiber, the material has good water retention, which can improve the crack resistance of the concrete and the anti-permeability of the road surface; second, the rheological properties of the water-absorbent sepiolite fiber can improve the operability of the construction and make the construction operation smoother; third, the stability of the properties of the water-absorbent sepiolite fiber material can enhance the durability of the fiber-recycled aggregate concrete, so that it can better adapt to various complex working environments.
[0011] Furthermore, it has been found that the water-absorbent sepiolite fiber in the raw material of rolled concrete can also work synergistically with the composite antifreeze agent to slow down the precipitation of ice crystals when it freezes, reduce the expansion stress of concrete and improve its durability. In the preparation process of concrete, it can also make up for the original defects of recycled aggregates and improve the operability of construction. Preferably, the amount of water-absorbent sepiolite fiber added to the raw material is 6.15wt.%-6.67wt.%.
[0012] Further, in the composite antifreeze provided by the present invention, in addition to the main components sodium thiocyanate, sodium oxalate and ethylene glycol, polyglycerol fatty acid ester and sodium gluconate are also added. Polyglycerol fatty acid ester is a nonionic surfactant of polyol esters, has the dual characteristics of hydrophilic and lipophilic, can significantly improve dispersibility and wettability, it can reduce the surface tension of water in concrete, make cement particles better dispersed in water, thereby improving the uniformity and density of fiber regeneration concrete. In addition, polyglycerol fatty acid ester can also improve the fluidity and workability of concrete system, and synergize with water-absorbing sepiolite fiber to reduce the bleeding and segregation phenomenon of concrete during pouring, so that texture and performance are more uniform and stable. Sodium gluconate mainly synergizes with polycarboxylic acid high-performance water-reducing agent in the present invention, can effectively reduce the water consumption of concrete, improve fluidity, extend the initial setting time of concrete, reduce slump loss, thereby reducing the risk of cracking during construction, improving the workability of concrete and the late strength of matrix.
[0013] Furthermore, it has been found that the addition amount of the composite antifreeze agent in the raw material is controlled within a reasonable range, which can maintain better mechanical properties and effectively reduce the mass loss rate under freeze-thaw cycle conditions. Preferably, the addition amount of the composite antifreeze agent in the raw material of the freeze-thaw resistant fiber recycled aggregate RCC is controlled to be 0.21wt.%-0.29wt.%.
[0014] Furthermore, it has been found through research that the ratio of ethylene glycol, sodium thiocyanate and sodium oxalate among the core components of the composite antifreeze also determines the application effect of the composite antifreeze. In the present invention, under the premise that the amount of composite antifreeze added in the raw materials of concrete remains unchanged, when the weight ratio of ethylene glycol, sodium thiocyanate and sodium oxalate is controlled to be 5:15:6, the anti-freeze and thaw effect of rolled concrete is most significantly improved.
[0015] Furthermore, the preparation method of the composite antifreeze comprises the following steps: firstly mixing sodium thiocyanate, sodium oxalate and part of water to obtain a mixed solution; then mixing the mixed solution with other raw materials of the composite antifreeze, and stirring at high speed to obtain a uniform solution, namely the composite antifreeze.
[0016] Furthermore, the cement is ordinary Portland cement, and the fly ash is primary fly ash.
[0017] Furthermore, the natural aggregate is fine sand with an average particle size of 0.25-0.35 mm.
[0018] Furthermore, the crushed recycled coarse aggregate has a particle size of 5-20 mm and is obtained by crushing and screening waste building materials. Preferably, in the crushed recycled coarse aggregate, the mass ratio of aggregate with a particle size of 5-10 mm to aggregate with a particle size of 10-20 mm is 4:6.
[0019] Furthermore, the water-absorbent sepiolite fiber is a fibrous magnesium-rich clay mineral, the fiber length of which is 2-3 mm, the weight water absorption rate is 160%-200%, and the density is 1-1.2 g / cm³.
[0020] Furthermore, the composite fiber aggregate is formed by mixing polypropylene fibers with a length of 25-30 mm and polyvinyl alcohol fibers in a mass ratio of 1:1.
[0021] The technical solution adopted by the present invention to achieve the second purpose is: to provide a method for preparing freeze-thaw resistant fiber recycled aggregate roller compacted concrete according to one of the purposes of the present invention, comprising the following steps: S1, mixing the rolled recycled coarse aggregate with silica fume, fly ash and part of water, and stirring at a certain rate to obtain pretreated rolled recycled coarse aggregate; S2, adding natural aggregate, cement, water-absorbing sepiolite fiber and composite fiber aggregate to the pretreated rolled recycled coarse aggregate in sequence, and continuing to stir to obtain a mixture; S3. Add the remaining water, composite antifreeze agent and polycarboxylic acid high-performance water reducing agent to the mixture, and continue stirring until uniformly mixed to obtain a freeze-thaw resistant fiber recycled aggregate roller compacted concrete.
[0022] In the above preparation method, first, silica fume and fly ash are added to partially fill the recycled aggregate to strengthen and seal the inherent cracks of the recycled aggregate; secondly, a composite fiber filler composed of polypropylene fiber and polyvinyl alcohol fiber is added to form a mesh structure inside the recycled concrete to improve the overall strength, toughness and durability; finally, a composite antifreeze agent, a water reducer and a retarder as well as a water-absorbing sepiolite fiber are added to improve the water retention and freeze-thaw resistance of the recycled concrete, promote the repair of the recycled aggregate, reduce the pores, slow down the precipitation of ice crystals during freezing, and reduce the expansion stress of the concrete, and finally obtain a fiber recycled aggregate roller compacted concrete with excellent mechanical properties and freeze-thaw resistance.
[0023] Furthermore, in step S1, the rolled recycled coarse aggregate is obtained by crushing and drying the waste building materials and then screening them, and is divided into two grades of rolled recycled coarse aggregate of 5-10 mm and 10-20 mm by screening equipment, and the mixing ratio of the two grades of recycled coarse aggregate with different particle sizes is 4:6.
[0024] Further, in step S1, the speed of the stirring treatment is 40-80 r / min, and the time is 4-6 h. Preferably, part of the water in step S1 accounts for 50% of the total weight of water in the raw material. Since the surface of the recycled coarse aggregate is coated with loose and fragile old mortar and contains a large number of cracks, high water absorption, and extremely poor anti-freeze-thaw effect, it is the key reason why the recycled coarse aggregate and its concrete have poor performance compared with general materials. It is necessary to modify and optimize it, but the traditional treatment method is not universal and is difficult to apply to actual engineering. In step S1 of the present invention, the physical performance enhancement of the target coarse aggregate using silica fume can effectively remove this original defect, improve its own strength and the performance of the concrete prepared therefrom. In addition, fly ash is added during the preparation process to further improve the impermeability, durability and antifreeze performance of the recycled coarse aggregate.
[0025] Furthermore, the composite antifreeze agent used in the present invention uses ethylene glycol, sodium thiocyanate and sodium oxalate as main antifreeze components. Ethylene glycol is combined with polyglycerol fatty acid ester and sodium gluconate to improve the bubbles introduced into the concrete during the mixing process and make them evenly arranged, thereby enhancing the water retention and fluidity of the concrete; the polycarboxylic acid high-performance water reducer, a polycarboxylic acid-based water reducer through an esterification process, can ensure the stable development of cement strength, and the sodium thiocyanate in the composite antifreeze agent can compensate for the strength loss caused by the use of the polycarboxylic acid water reducer; the water-absorbing sepiolite fiber can synergistically act with the composite antifreeze agent to slow down the precipitation of ice crystals when it is frozen, reduce the expansion stress of the concrete, and improve its durability. In the preparation process of the concrete, it can also make up for the original defects of the recycled aggregate and improve the operability of the construction.
[0026] The technical solution adopted by the present invention to achieve the third purpose is: to provide an application of the freeze-thaw-resistant fiber recycled aggregate rolled concrete described in one of the purposes of the present invention, or the freeze-thaw-resistant fiber recycled aggregate rolled concrete prepared by the preparation method described in the second purpose of the present invention, and the application includes: constructing the prepared freeze-thaw-resistant fiber recycled aggregate rolled concrete by means of through-warehouse thin layer pouring and vibration rolling.
[0027] The freeze-thaw resistant fiber recycled aggregate roller compacted concrete provided by the present invention is a dry hard cement-poor concrete, which has many difficulties and inconveniences in construction using traditional methods. The present invention uses the method of through-storage thin layer pouring and vibration rolling for construction, which can speed up the construction progress. Through the through-storage thin layer pouring, the heat dissipation effect is enhanced, the density of the concrete is ensured, the engineering workload is reduced, and the warehouse surface operation is simplified, which is conducive to speeding up the construction progress. In addition, the through-storage thin layer pouring and vibration rolling method can reduce the amount of cement used and increase the amount of fly ash added, thereby reducing the project cost. At the same time, this construction method can also reduce energy consumption and environmental pollution by optimizing material use and construction technology.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The freeze-thaw resistant fiber recycled aggregate roller compacted concrete provided by the present invention is composed of rolled recycled coarse aggregate, cement, silica fume, fly ash, natural aggregate, water-absorbent sepiolite fiber, water, composite fiber aggregate, composite antifreeze agent and polycarboxylic acid high-performance water reducer. The addition of silica fume and fly ash can repair the cracks on the surface of the recycled coarse aggregate, remove this original defect, and improve the compressive strength of the concrete; the composite fiber can strengthen the adhesion between the aggregates, significantly improve the crack resistance, basic mechanical properties and durability of the matrix; the water-absorbent sepiolite fiber can improve its water retention, construction operability and durability of the matrix; the composite antifreeze agent can greatly improve the freeze-thaw resistance of the fiber recycled aggregate concrete while enhancing the water retention of the concrete and the mechanical properties and durability of the matrix. The various materials in the freeze-thaw resistant fiber recycled aggregate roller compacted concrete of the present invention can influence each other and work synergistically, thereby achieving the improvement of the freeze-thaw resistance of the fiber recycled aggregate roller compacted concrete.
[0029] (2) In view of the insufficient resource utilization of existing construction waste, the present invention provides a freeze-thaw resistant fiber recycled aggregate rolled concrete and a preparation method thereof. The prepared rolled concrete not only has excellent mechanical properties, impact resistance, wear resistance, and freeze-thaw resistance, but also has the advantages of simple preparation method, low cost, low construction requirements, and high efficiency. It has good application value in actual engineering, can realize large-scale and efficient utilization of construction waste, and has significant environmental effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention provides a schematic flow chart of a method for preparing and constructing freeze-thaw resistant fiber recycled aggregate roller compacted concrete. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0033] The invention provides a freeze-thaw resistant fiber recycled aggregate rolled concrete, which is composed of the following raw materials by weight: 400-455 parts of rolled recycled coarse aggregate; 140-160 parts of cement; 14-18 parts of silica fume; 30-38 parts of fly ash; 195-225 parts of natural aggregate; 50-65 parts of water-absorbing sepiolite fiber; 50-70 parts of water; 2-4 parts of composite fiber aggregate; 1.25-3.6 parts of composite antifreeze agent; 1-1.5 parts of polycarboxylic acid high-performance water reducer; The composite antifreeze agent is composed of the following raw materials by weight: 0.05-0.15 parts of ethylene glycol; 0.05-0.15 parts of sodium thiocyanate; 0.04-0.08 parts of sodium oxalate; 0.1-0.2 parts of polyglycerol fatty acid ester; 0.01-0.05 parts of sodium gluconate; and 1-3 parts of water.
[0034] The process diagram of the preparation method and construction method of the freeze-thaw resistant fiber recycled aggregate roller compacted concrete is as follows Figure 1 shown.
[0035] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0036] The weight proportions of the raw materials of the freeze-thaw resistant fiber recycled aggregate roller compacted concrete in Examples 1-5 of the present invention are shown in Table 1 below: Table 1
[0037] In the above table, cement is ordinary Portland cement, fly ash is first-grade fly ash, natural aggregate is fine sand with an average particle size of 0.25-0.35 mm; the particle size of rolled recycled coarse aggregate is 5-20 mm, which is obtained by crushing and screening waste building materials; absorbent sepiolite fiber is a fibrous magnesium-rich clay mineral with a fiber length of 2-3 mm, a weight water absorption rate of 160%-200%, and a density of 1-1.2 g / cm³; the composite fiber aggregate is a mixture of polypropylene fiber with a length of 25-30 mm and polyvinyl alcohol fiber in a mass ratio of 1:1.
[0038] In the composite antifreeze prepared in Example 1 and Examples 6-14, the amount of each raw material used is shown in Table 2 below (in kg).
[0039] Table 2
[0040] Example 1 The following raw materials are weighed in parts by weight: 400 kg rolled recycled coarse aggregate; 140 kg ordinary Portland cement; 14 kg silica fume; 30 kg first-grade fly ash from industrial waste; 200 kg natural aggregate; 55 kg water-absorbent sepiolite fiber; 50 kg water; 2 kg composite fiber aggregate; 2.38 kg composite antifreeze agent (the amount added to the raw materials is 0.27 wt.%); and 1.5 kg polycarboxylic acid high-performance water-reducing agent.
[0041] The preparation of the composite antifreeze agent consists of the following components: 0.05 kg ethylene glycol, 0.15 kg sodium thiocyanate, 0.06 kg sodium oxalate, 0.1 kg polyglycerol fatty acid ester, 0.02 kg sodium gluconate, and 2 kg water.
[0042] The composite antifreeze is prepared by the following steps: (1) Under the environment of 20±5℃, sodium thiocyanate, sodium oxalate and part of water (40% of the total amount) are mixed and stirred for 3-5 minutes to obtain a mixed solution A; (2) Mix the mixed solution A with ethylene glycol, polyglycerol fatty acid ester, sodium gluconate and the remaining water (60% of the total amount), and stir at high speed until the solution is uniform to obtain a composite antifreeze.
[0043] The preparation method and construction method of the freeze-thaw resistant fiber recycled aggregate roller compacted concrete are as follows: Step 1: weigh ordinary Portland cement, silica fume, industrial waste slag first-grade fly ash, water, natural aggregate, rolled recycled coarse aggregate, water-absorbing sepiolite fiber, composite fiber aggregate, composite antifreeze agent, and polycarboxylic acid high-performance water reducer according to the weight proportions of each raw material shown in Table 1; Step 2: After the waste building materials are crushed and dried, they are screened and divided into two grades of 5-10mm and 10-20mm crushed recycled coarse aggregates through screening equipment, and the mixing ratio of the two grades of recycled coarse aggregates with different particle sizes is 4:6; Step 3: Place the rolled recycled coarse aggregate obtained in step 2 in a concrete mixer drum, and stir with weighed silica fume, industrial waste slag first-grade fly ash and part of water (50% of the total amount) at a speed of 60 r / min for 5 hours to enhance the physical performance of the recycled coarse aggregate; Step 4: Add natural aggregate, silicate cement and composite fiber aggregate into the mixer in sequence and mix until uniform; Step 5: Add the remaining water (50% of the total amount), composite antifreeze agent and polycarboxylic acid high-performance water reducing agent into the mixer, and continue to stir until the freeze-thaw-resistant fiber recycled aggregate roller compacted concrete is prepared evenly; Step 6: The freeze-thaw resistant fiber recycled aggregate roller compacted concrete prepared in step 5 is then constructed by pouring a thin layer through the warehouse and vibrating and compacting.
[0044] Embodiment 2-5 The freeze-thaw resistant fiber recycled aggregate roller compacted concrete was prepared according to the weight percentage of each raw material shown in Table 1. In the raw materials of the composite antifreeze used in Examples 2-5, the mass ratio of ethylene glycol, sodium thiocyanate, sodium oxalate, polyglycerol fatty acid ester, sodium gluconate and water was 5:15:6:10:2:200 (consistent with Example 1). In Examples 2-5, the addition amount of the composite antifreeze to the concrete raw materials was 0.21wt.%, 0.29wt.%, 0.35wt.% and 0.13wt.%, respectively.
[0045] The preparation method of the composite antifreeze agent, the preparation method of the freeze-thaw resistant fiber recycled aggregate roller compacted concrete and the construction method are all consistent with those in Example 1.
[0046] Embodiment 6-14 Except for the composite antifreeze, the amounts of other raw materials in the freeze-thaw resistant fiber recycled aggregate RCC are consistent with those in Example 1. In Examples 6-14, the amounts of each raw material in the composite antifreeze are shown in Table 2, and the preparation method of the composite antifreeze, the preparation method of the freeze-thaw resistant fiber recycled aggregate RCC and the construction method are consistent with those in Example 1.
[0047] Examples 15-17 The difference between Examples 15-17 and Example 1 is that the amount of water-absorbing sepiolite fiber in the raw material for preparing freeze-thaw-resistant fiber recycled aggregate RCC in Example 1 is adjusted to 50kg, 60kg and 65kg respectively, and the other conditions and preparation methods are consistent with Example 1.
[0048] Embodiment 18 The difference between this embodiment and embodiment 1 is that in the preparation method of freeze-thaw resistant fiber recycled aggregate RCC, the physical performance strengthening step of step 3 is cancelled, and silica fume and fly ash are directly mixed together instead of part of the cement, and the other conditions and preparation method are consistent with those of embodiment 1.
[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that the raw materials of the freeze-thaw resistant fiber recycled aggregate RCC do not contain a composite antifreeze agent, and the other conditions and preparation methods are consistent with those of Example 1.
[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that 55 kg of water-absorbent sepiolite fiber in the raw materials of freeze-thaw-resistant fiber recycled aggregate RCC is replaced by a mixture of fly ash and silica fume of equal weight (the weight ratio of the two is 1:1), and the other conditions and preparation methods are consistent with Example 1.
[0051] Performance evaluation indicators and test plans The performance tests were conducted on the roller compacted concrete prepared in the embodiments of the present invention and the comparative examples, and the test contents included a compressive strength test and a freeze-thaw cycle test.
[0052] (1) Compressive strength test: Each group of designed specimens consists of 2 groups of 3 cubes with a size of 100 mm × 100 mm × 100 mm. The test blocks are cured at room temperature for 28 days. After the curing period, the mechanical properties of the concrete test blocks that have not been subjected to freeze-thaw cycle treatment and those that have been subjected to freeze-thaw cycle treatment are tested in accordance with the Standard Test Method for Mechanical Properties of Ordinary Concrete.
[0053] (2) Freeze-thaw cycle test: Test specimens were prepared according to the proportions of Examples 1-18 and Comparative Examples 1 and 2. The sample size used in this freeze-thaw test was a prism of 100 mm × 100 mm × 400 mm, with 3 sample specimens in each group, and cured for 28 days. According to the specific requirements of the standard "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the initial mass and initial dynamic elastic modulus of the sample were measured before freeze-thaw, and the freeze-thaw test was started immediately. In the freeze-thaw cycle test, the temperature variation range of the sample center was -18 ± 2 ° C to 5 ± 2 ° C, each freeze-thaw cycle was 4 hours, and the sample was thawed for no less than 1 hour in each cycle.
[0054] During the test, the damage of the specimens was observed after every 25 freeze-thaw cycles, and the mass and dynamic elastic modulus were measured. Uniaxial compression stress and strain were collected after every 100 freeze-thaw cycles. The relative durability index of the concrete specimens was calculated based on the weight loss rate and relative dynamic elastic modulus to measure the antifreeze durability of the recycled concrete.
[0055] The test results of relevant performance are shown in Table 3 below: Table 3
[0056] As can be seen from the above table, Before experiencing freeze-thaw cycles, the 28-day compressive strength of Examples 1-18 was 34.41 MPa-43.98 MPa, showing relatively excellent mechanical properties; at the same time, the relative dynamic elastic modulus and mass loss rate of the sample specimens of Examples 1-18 after experiencing 250 freeze-thaw cycles were 72.6%-82.5% and 2.83%-3.84%, respectively, and the antifreeze performance was significantly better than that of the samples of Comparative Examples 1 and 2.
[0057] Comparing the test results of Examples 1-5, it can be seen that the amount of composite antifreeze added in the formula system has an important influence on the antifreeze performance, which can promote the dissolution of various ions in the early stage of recycled aggregate concrete and improve the fluidity and water retention of concrete mixtures; the early bonding process also reduces the freezing point of concrete, thereby playing a good role in early strength and antifreeze. Further, the addition of composite antifreeze enhances its density and uniformity while promoting the stability of the structure as soon as possible, so that it reduces cracking and improves basic mechanical properties and durability during later use, thereby ultimately significantly improving the antifreeze performance of recycled concrete. For the amount of composite antifreeze added in the raw material, if the amount is low, it will lead to poor fusion of its components in the early stage, and the structural performance in the later stage cannot be guaranteed; if the amount is too high, not only can the antifreeze performance of concrete not be further improved, but the excessive addition of the components of the composite antifreeze leads to a decrease in compressive strength. Based on the above analysis, when the amount of composite antifreeze added in the concrete raw material is controlled to be 0.21wt.%-0.29 wt.%, the antifreeze effect is better.
[0058] Further, by comparing the test results of Example 1 and Example 6-13, it can be seen that the test performance of the rolled concrete shows the following rules with the adjustment of the main effective components of the composite antifreeze liquid: the compressive strength decreases with the increase of the ethylene glycol content, and the strength is the highest when the ethylene glycol content is 0.5Kg; the compressive strength of the concrete decreases slightly first and then sharply decreases with the increase of the sodium thiocyanate content; the compressive strength of the concrete increases first and then decreases with the increase of the sodium oxalate content, and when the sodium oxalate content is 0.6Kg, the strength of the concrete reaches the best. In summary, considering the actual needs of the project, among the core components of the composite antifreeze liquid, under the condition of controlling the mass ratio of ethylene glycol, sodium thiocyanate and sodium oxalate to 5:15:6, the synergistic effect of the three is the best, which greatly improves the antifreeze durability of the fiber recycled aggregate rolled concrete, and has a small impact on its compressive strength. At the same time, under this ratio, the antifreeze performance of the antifreeze-thaw fiber recycled aggregate rolled concrete is greatly improved. In addition, by comparing the test results of Example 1 and Example 14, it can be seen that in the composition of the composite antifreeze, a reduction in the content of sodium gluconate will also affect its compressive strength and other indicators. Therefore, it is best to control the mass ratio of ethylene glycol, sodium thiocyanate, sodium oxalate, and sodium gluconate to 5:15:6:0.2.
[0059] Comparing the test results of Example 1 with those of Examples 14-16, it can be seen that in the formula system of the present invention, as the amount of water-absorbent sepiolite fiber increases, its compressive strength and antifreeze performance both show a trend of first increasing and then decreasing, reaching the optimum at 60 kg. It is also found that the water-absorbent sepiolite fiber has a great improvement in the antifreeze durability of concrete, but due to its good water absorption rate, excessive incorporation will cause the compressive strength and antifreeze durability of concrete to decrease to a certain extent. Therefore, controlling the water-absorbent sepiolite fiber in the raw material formula system within the range of 6.15wt.%-6.67wt.% is helpful to further improve the mechanical properties and antifreeze durability of the roller compacted concrete.
[0060] By comparing the test results of Example 1 with those of Example 17, it can be seen that when the recycled coarse aggregate is first coated with silica fume and fly ash, its compressive strength, relative dynamic elastic modulus and mass loss rate are better than those of the untreated sample. This proves that this pretreatment step can effectively remove the original defects such as loose and fragile old mortar and inherent cracks on the surface of the recycled coarse aggregate, thereby improving its compressive strength and durability to a certain extent.
[0061] Comparing the test results of Example 1 with those of Comparative Example 1, it can be seen that the composite antifreeze liquid added to the raw materials of Example 1 has no adverse effect on the mechanical properties of the fiber recycled aggregate RCC, and the compressive strength is basically consistent with that of Comparative Example 1 without the composite antifreeze liquid. However, after 250 freeze-thaw cycles, the relative dynamic elastic modulus and mass loss rate of the test piece prepared in Example 1 with the composite antifreeze liquid added are significantly better than those without the composite antifreeze liquid.
[0062] Comparing the test results of Example 1 with those of Comparative Example 2, it can be seen that although the compressive strength can be improved by using silica fume and fly ash instead of sepiolite fiber, its antifreeze performance is greatly reduced. This shows that in the present invention, the adsorption and good water retention of water-absorbing sepiolite fiber can improve its durability, and can work synergistically with the composite antifreeze agent to slow down the precipitation of ice crystals when freezing and reduce the expansion stress of concrete and improve its durability. In the preparation process of concrete, it can also make up for the original defects of recycled aggregate and improve the operability of construction.
[0063] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A freeze-thaw resistant fiber recycled aggregate roller compacted concrete, characterized in that: The invention is composed of the following raw materials by weight: 400-455 parts of rolled recycled coarse aggregate; 140-160 parts of cement; 14-18 parts of silica fume; 30-38 parts of fly ash; 195-225 parts of natural aggregate; 50-65 parts of water-absorbing sepiolite fiber; 50-70 parts of water; 2-4 parts of composite fiber aggregate; 1.25-3.6 parts of composite antifreeze agent; 1-1.5 parts of polycarboxylic acid high-performance water reducing agent; The composite antifreeze agent is composed of the following raw materials by weight: 0.05-0.15 parts of ethylene glycol; 0.05-0.15 parts of sodium thiocyanate; 0.04-0.08 parts of sodium oxalate; 0.1-0.2 parts of polyglycerol fatty acid ester; 0.01-0.05 parts of sodium gluconate; and 1-3 parts of water.
2. The freeze-thaw resistant fiber recycled aggregate roller compacted concrete according to claim 1, characterized in that: The preparation method of the composite antifreeze comprises the following steps: firstly mixing sodium thiocyanate, sodium oxalate and part of water to obtain a mixed solution; then mixing the mixed solution with other raw materials of the composite antifreeze, and stirring at high speed to obtain a uniform solution, namely the composite antifreeze.
3. The freeze-thaw resistant fiber recycled aggregate RCC according to claim 1, characterized in that: The cement is ordinary Portland cement, and the fly ash is primary fly ash.
4. The freeze-thaw resistant fiber recycled aggregate RCC according to claim 1, characterized in that: The natural aggregate is fine sand with an average particle size of 0.25-0.35 mm.
5. The freeze-thaw resistant fiber recycled aggregate RCC according to claim 1, characterized in that: The particle size of the rolled recycled coarse aggregate is 5-20 mm, and is obtained by crushing and screening waste building materials.
6. The freeze-thaw resistant fiber recycled aggregate RCC according to claim 1, characterized in that: The water-absorbent sepiolite fiber is a fibrous magnesium-rich clay mineral, with a fiber length of 2-3 mm, a weight water absorption rate of 160%-200%, and a density of 1-1.2 g / cm³.
7. The freeze-thaw resistant fiber recycled aggregate RCC according to claim 1, characterized in that: The composite fiber aggregate is formed by mixing polypropylene fibers with a length of 25-30 mm and polyvinyl alcohol fibers in a mass ratio of 1:
1.
8. A method for preparing freeze-thaw resistant fiber recycled aggregate roller compacted concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing the rolled recycled coarse aggregate with silica fume, fly ash and part of water, and stirring at a certain rate to obtain pretreated rolled recycled coarse aggregate; S2, adding natural aggregate, cement, water-absorbing sepiolite fiber and composite fiber aggregate to the pretreated rolled recycled coarse aggregate in sequence, and continuing to stir to obtain a mixture; S3. Add the remaining water, composite antifreeze agent and polycarboxylic acid high-performance water reducing agent to the mixture, and continue stirring until uniformly mixed to obtain a freeze-thaw resistant fiber recycled aggregate roller compacted concrete.
9. The preparation method according to claim 8, characterized in that In step S1, the stirring process is performed at a speed of 40-80 r / min for 4-6 h.
10. An application of the freeze-thaw resistant fiber recycled aggregate RCC according to any one of claims 1 to 7, or the freeze-thaw resistant fiber recycled aggregate RCC prepared by the preparation method according to claim 8 or 9, characterized in that: The freeze-thaw resistant fiber recycled aggregate roller compacted concrete is constructed by means of through-storage thin layer pouring and vibration rolling.
Citation Information
Patent Citations
Heat insulating and anti-cracking plastering dry mortar powder
CN101759415A
Roller-compacted concrete and preparation method thereof
CN109553333A
Modified asphalt and high-strength water-permeable asphalt concrete containing asphalt
CN109970391A
Concrete surface thermal insulation material as well as preparation method and use method thereof
CN114407476A
Preparation process of anti-freezing recycled concrete
CN115745484A
